The role of forestry measures in the formation of highly productive mixed oak forest - Agiy , V.O.; Kopiy, S.L.; Kaganyak, Yu.Y.; Kopiy, L.I.; Kopiy, M.I.; Novak, A.A.; Fizyk-Nadsluchansjkyy, I.V. (Forestry, Forest, Paper and Woodworking Industry, 2019)
Reproduction of highly productive mixed oak stands is a responsible task, both for the practice of forestry and in the theoretical sense. Intensification of forestry activities requires the formation of not only stands with the maximum stock, appropriate assortment structure, but also environmentally sustainable mixed with the dominance of oak. This task involves finding the best option for felling. The existing system of care felling does not give an unambiguous answer to the task. Conducting experimental felling care at a young age with different options for sampling of secondary trees and the intensity of felling, contribute to the development of technology for the care of oak at a young age, when determining its role in shaping future high-yielding and environmentally sustainable oak forest. Practical recommendations are preceded by research on the course of growth in stationary test plots. The purpose of experimental care felling is to investigate the impact of forestry measures implemented in sections of the experimental plots on the growth processes of mixed oak stands at the stage of young trees of the first class age (up to 10 years). The object of research is selected mixed oak forest stands growing on the territory of the state forest fund of forestry enterprises of Transcarpathia. The subject of the study is the dynamics of taxonomic indicators of mixed oak young trees of the first class of age in six sections of the stationary. The section of the plot with the best growth characteristics of both stand and oak is determined. The dynamics during 2017-2019 of the average trunk volume, diameter and height of oak, etc. was studied. The program of forestry measures implemented at the section C-1 of the plot, where a reliable oak element of the forest with an admixture of hornbeam and ash was formed, was adopted as the optimal variant. Adequate models for predicting the average volume of an oak trunk depending on the average diameter or height are offered. The high adequacy of the model guarantees a more accurate assessment of the stock accumulated by ordinary oak.